An economic analysis of online streaming: How the music industry can generate revenues from cloud computing - Tim Paul Thomes (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper investigates the upcoming business model of online streaming services allowing music consumers either to subscribe to a service which provides free-of-charge access to streaming music and which is funded by advertising, or to pay a monthly flat fee in order to get ad-free access to the content of the service accompanied with additional benefits. Both businesses will be launched by a single provider of streaming music. By imposing a two-sided market model on the one hand combined with a direct transaction between the streaming service and its flat-rate subscribers on the other hand, the investigation shows that it can be highly profitable to launch a business which is free-of-charge for subscribers if advertising imposes a weak nuisance to music consumers. If this is the case, and by imposing an endogenously determined level of advertising which will be provided by homogeneous advertisers, the analysis shows that the monopolistic streaming service increases the price for its flat-rate subscribers in order to stimulate free-of-charge demand and to capture higher revenues from advertisers. An extension of the model by illegal file-sharing reveals that an increase in copyright enforcement shifts rents from music consumers to the monopolistic provider, moreover a maximal punishment for piracy will be welfare-maximizing.
Older version: http://hdl.handle.net/10419/48156
Keywords: D42; L12; L82; 330; Advertising media; Music industry; Online streaming; Piracy; Musikwirtschaft; Internet; Online-Werbung; Geschäftsmodell; Cloud Computing; Betriebliche Preispolitik; Urheberrecht; Theorie